Financial Analysis of AstraZeneca Company (Finanční analýza společnosti AstraZeneca) - Maidaniuk, Varvara (2025)
This bachelor's thesis focuses on the financial analysis of the AstraZeneca company. The thesis aims to assess the company's financial health and compare it to other companies within the same branch. Financial analysis is carried out based on the annual reports from 2019 to 2023. In the first part, AstraZeneca and its competitors are described. Financial analysis is then conducted, including calculating absolute indicators and ratio analysis. Afterwards, strategic analysis with internal and external potential analysis is conducted. The conclusion includes an AstraZeneca company financial health evaluation.